A Study on Customer Knowledge For Internet Banking: Exploring Factors and Perception of Internet Banking (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Internet banking is becoming is increasingly becomingpopular because of convenience and flexibility. The present paper explores themajor factors responsible for internet banking based on respondents’ perceptionon various internet applications. It also provides a framework of the factorswhich are taken to assess the internet banking perception.